2015
DOI: 10.1038/srep17342
|View full text |Cite
|
Sign up to set email alerts
|

Impaired ATP6V0A2 expression contributes to Golgi dispersion and glycosylation changes in senescent cells

Abstract: Many genes and signaling pathways have been found to be involved in cellular senescence program. In the present study, we have identified 16 senescence-associated genes by differential proteomic analysis of the normal human diploid fibroblast cell line, TIG-1, and focused on ATP6V0A2. The aim of this study is to clarify the role of ATP6V0A2, the causal gene for ARCL2, a syndrome of abnormal glycosylation and impaired Golgi trafficking, in cellular senescence program. Here we showed that ATP6V0A2 is critical fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 28 publications
1
25
0
Order By: Relevance
“…Loss of Oglycosylation in epithelial cells reduces the secretion of basement membrane collagen protein that affects ECM composition in submandibular gland in mice (Tian et al, 2012). Further, upon inhibition of V-ATPase function, Golgi pH and structure are disrupted and glycosyltransferases are relocated from Golgi to early endosomes or plasma membranes, resulting in glycosylation changes (Hucthagowder et al, 2009;Kellokumpu et al, 2002;Udono et al, 2015). Our results are consistent with these studies as we found a similar glycosylation and compositional defects in ECM and dispersed Golgi morphology in mammary epithelial cells of a2V fl/fl MMTV Cre mice breast tissues.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Loss of Oglycosylation in epithelial cells reduces the secretion of basement membrane collagen protein that affects ECM composition in submandibular gland in mice (Tian et al, 2012). Further, upon inhibition of V-ATPase function, Golgi pH and structure are disrupted and glycosyltransferases are relocated from Golgi to early endosomes or plasma membranes, resulting in glycosylation changes (Hucthagowder et al, 2009;Kellokumpu et al, 2002;Udono et al, 2015). Our results are consistent with these studies as we found a similar glycosylation and compositional defects in ECM and dispersed Golgi morphology in mammary epithelial cells of a2V fl/fl MMTV Cre mice breast tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Golgi morphology and defective glycosylation in mammary epithelial cells Next, we examined how the deletion of a2V leads to a low production of ECM proteins. a2V is present on Golgi membrane and disruption of a2V functions leads to deformation in Golgi structure (Axelsson et al, 2001;Udono et al, 2015). We evaluated Golgi morphology in mammary epithelial cells of breast tissues from a2V fl/fl MMTV Cre mice by staining for giantin, which is a Golgi membrane protein.…”
Section: Inhibition Of A2v Expression Causes Alteredmentioning
confidence: 99%
See 1 more Smart Citation
“…Alterations of this important post‐translational event are also described in some progeroid syndromes and age‐associated pathologies . Moreover, secretion and glycosylation modifications have also been reported in senescent skin cells . Changes in protein secretion have been observed during skin ageing resulting in a specific secretome, named skin ageing–associated secreted proteins (SAASP), which are produced by dermal fibroblasts obtained from old donors .…”
Section: Introductionmentioning
confidence: 99%
“…The structure of the Golgi apparatus undergoes changes during biological processes, including secretion, mitosis, apoptosis and age‐related diseases, including cancer or Alzheimer pathologies . Alterations of the Golgi morphology have been reported in the mouse brain during ageing and in senescent human cell lines …”
Section: Introductionmentioning
confidence: 99%